Strategi Marketing Public Relations dalam Membangun Citra Lembaga Pendidikan - Utomo, Shandra Fitriani; Heni Hayat; Novi Andayani Praptiningsih (Communicology: Jurnal Ilmu Komunikasi, 2025)
The large number of private schools and the competitiveness and challenges of public relations and other private schools. Schools compete to provide students and parents the best education and services. The Al Muslim Foundation is an educational institution that continues to innovate and be creative, with the digital Islamic school as its latest image. In the face of this, one strategy, namely the marketing public relations strategy, can be used. The purpose of this study is to understand and know how the marketing strategy of public relations Al Muslim Foundation is in building image. The Three Ways Strategy by Thomas L. Harris. This is the push strategy, the pull strategy, and the pass strategy. This study uses qualitative methods with a   descriptive approach. The results of this research indicate that the marketing public relations strategy carried out by the Al Muslim Foundation in building its image is relevant to the Three Ways Strategy concept, but in the process, there are still some disadvantages. The conclusion of this study shows that among the three strategies, push, pull, and pass the pass strategy provides the most positive contribution to building the image of educational institutions.